Analysis Of the Influence of Financial Technology Peer-To-Peer (P2P) Lending and Payment Gateway on The Financial Performance Of MSMES In Pematangsiantar City - Mahaitin H Sinaga; Wico J Tarigan; Sri Martina (Program Studi Akuntansi Universitas Simalungun, 2025)
This study examines the influence of financial technology specifically Peer-to-Peer (P2P) Lending and Payment Gateway services on the financial performance of micro, small, and medium enterprises (MSMEs) operating within the Siantar Square culinary center in Pematangsiantar, Indonesia. Primary data were collected from 32 MSME respondents through a purposive sampling technique using structured questionnaires. The analysis employed validity and reliability tests, normality testing, multiple linear regression, partial t-tests, and simultaneous F-tests to assess the impact of the fintech variables. The findings reveal that P2P Lending does not exert a significant partial effect on MSME financial performance, indicating that digital lending has not yet translated into measurable financial improvement for local businesses. Conversely, Payment Gateway usage demonstrates a positive and significant effect, suggesting that digital payment systems enhance transaction efficiency, cash-flow management, and overall financial performance. The simultaneous F-test further confirms that both fintech variables collectively influence financial outcomes, with Payment Gateway acting as the dominant contributing factor. These results underscore the strategic importance of digital payment adoption, improved digital financial literacy, and supportive digital ecosystems in strengthening MSME financial performance in emerging regional markets